Legitimizing violence by protestors and the police in social protests: The case of Chile, 2019-2022 - Ross Zbinden, Maximiliano Agustín; Navia, Patricio Daniel (Revista Latinoamericana de Opinión Pública, 2024)
Based on a theoretical discussion on the legitimation of violence, we postulate 4 hypotheses on the determinants of the legitimation of acts of violence perpetrated by protests and state agents in popular manifestations in Chile. We test them using polling data from national surveys conducted by the Center for Public Studies between 2019 and 2022. Marches enjoy more legitimation than other forms of violence by protestors. We find a reduction in the legitimation of violence by protests and an increase in the legitimation of violence by state agents in 2021 and 2022 compared to 2019. Those who trust less the Carabineros police and those who believe that the armed forces violated human rights legitimize more all forms of violence by protestors and less the violence by state agents. Right-wingers legitimize violence by state agents more, and leftwingers legitimize violence by protestors more and less that by state agents.